Operational research techniques - White, D. J.; Donaldson, William Anderson; Lawrie, Norman (London : Business Books, 1969)
The book presents the ways in which the basic conflicts in a decision situation can be formalised ,a group of techniques which have been developed
Vol. 1 has subtitle: An introduction.
Includes bibliographical references.
obn25/01/2019
Loans
Keywords: Operations research; Production management